1969
DOI: 10.1099/00221287-56-2-157
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Analysis of Streptococcus bovis, Strain s19, Cell Walls

Abstract: S U M M A R YTwo antigens, a glucose-rich capsular polymer and a cell wall carbohydrate consisting of N-acetylglucosamine, glucose and rhamnose, were isolated from Streptococcus bovis, strain s 19. N-acetylglucosamine and a haptenic fraction rich in glucosamine inhibited approximately 56 and 63 of the quantitative precipitin reaction between the s 19 cell wall carbohydrate and its homologous antiserum, respectively. A cross-reactivity between a preparation of azo-protein, which consisted of terminal P-N-acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…A noticeable feature of the results was that all the three encapsulated strains of S. bovis (including Sb‐5) had similar CRIs (range: 7.3–12.4%), which were significantly lower than the CRIs of the non‐encapsulated strains (range: 28.9–56.1%). This is consistent with the earlier observations that both cell wall and capsule materials may contribute to the antigenicity of S. bovis [22–24]. The higher CRIs of the non‐capsulate strains may be due to the lack of capsular antigens of these strains since the antiserum for this study was prepared from cattle immunised with a vaccine containing encapsulated S. bovis strain Sb‐5 cells.…”
Section: Discussionsupporting
confidence: 90%
“…A noticeable feature of the results was that all the three encapsulated strains of S. bovis (including Sb‐5) had similar CRIs (range: 7.3–12.4%), which were significantly lower than the CRIs of the non‐encapsulated strains (range: 28.9–56.1%). This is consistent with the earlier observations that both cell wall and capsule materials may contribute to the antigenicity of S. bovis [22–24]. The higher CRIs of the non‐capsulate strains may be due to the lack of capsular antigens of these strains since the antiserum for this study was prepared from cattle immunised with a vaccine containing encapsulated S. bovis strain Sb‐5 cells.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, colonization and antibody response of pigeons immunized with an SGP strain containing a thin irregular capsule (PDH 827) did not protect against a high-virulent strain SGG strain with a thick capsule (STR357). These findings indicate that supernatant proteins, glycans, fimbriae and the capsule may be involved in the induction of protective immunity against SGG infections but likely not across SBSEC species (Kane and Karakawa, 1969 ; Kane et al, 1972 ; Pazur and Forsberg, 1978 ; Pazur et al, 1978 ; Vanrobaeys et al, 1997 ; Kimpe et al, 2002 ).…”
Section: Clinical Infections and Host-immune Response Due To Sbsec Inmentioning
confidence: 99%
“…Schleifer and Kandler also have shown that S. cremoris 316a and 331a possess an L-alanyl-threonine dipeptide bridge (20). Recently, Kane et al reported that the mucopeptide of S. bovis, a member of the group D streptococci, contains a high concentration of threonine (7).…”
mentioning
confidence: 99%